Online Dating as A Strategic Game Why and How Men in Hong Kong Use QQ to Chase Women in Mainland China - Choi, Maurice Kwok-to.; Chan, Kwok-bun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Based on a study using online ethnography as the major research method, this book explains why and how men in Hong Kong use QQ$1 (Ban online instant messenger$1 (Bto (3z(Bchase(3y (Bwomen in mainland China, especially in the neighboring city of Shenzhen. Chasing women through QQ is a reciprocal exchange process during which the resources to be exchanged in the interaction are not negotiated. Rather, the men provide resources to the women, hoping for rewards in return that are not guaranteed. This characteristic of the exchange makes men who chase women through QQ very strategic in their action. They try to maximize the rewards and minimize the costs by adopting myriad strategies, such as constructing an attractive online identity by strategic self-presentation. The role of emotions in the exchange process is also examined. Men learn the emotional norms through the online forum, but sometimes it is difficult for them to control their emotions; some men fall in love when they are not supposed to. As it happens, they have failed to calculate the costs and rewards rationally in that they may provide too many resources to the women without getting enough rewards in return. This book provides original insights into the thought processes, motivations, desires, anxieties and risks of Hong Kong men seeking short-term sexual relations with women on the mainland. These insights are highly relevant to our understanding of the quickly evolving use of social media, a phenomenon of worldwide importance and deep implications.s
List of Tables -- List of Figures -- Chapter 1 : Introduction -- Chapter 2 : Exchange, Emotions, Intimacy, Masculinities, Love, Money and Cyberlove -- Chapter 3 : Methodology and Internet Research Methods -- Chapter 4 : Invitation to the QQ World -- Chapter 5 : The Beginning of the Chasing Game -- Chapter 6 : The Dramatic Moment of the Chasing Game: When a Man Meets a Woman -- Chapter 7 : The Feelings of the Men: Looking into an Inner World -- Chapter 8 : Conclusion -- Appendix -- References.
Keywords: Social sciences; Social Sciences; Media Research